2012
DOI: 10.1029/2012gc004120
|View full text |Cite
|
Sign up to set email alerts
|

Pyrite alteration and neoformed magnetic minerals in the fault zone of the Chi‐Chi earthquake (Mw7.6, 1999): Evidence for frictional heating and co‐seismic fluids

Abstract: During an earthquake, physical and chemical transformations lead to alteration and formation of minerals in the gouge layer. Altered and neoformed minerals can be used as tracers of some earthquake processes. In this study, we investigate pyrite and magnetic minerals within the host Chinshui siltstone and the 16‐cm‐thick gouge. This gouge hosts the principal slip zone of Chi‐Chi earthquake (Mw7.6, 1999). In the Chinshui siltstone, pyrite framboids of various sizes and euhedral pyrite are observed. The magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 102 publications
(164 reference statements)
1
49
0
Order By: Relevance
“…Although the pH of interstitial fluid along the slip zone was not measured, it was reported that pyrite was absent in the slip zone35. Because pyrite dissolution would lower the pH of the immediately surrounding sediment36, we used pH values of 3.0 and 6.0.…”
Section: Resultsmentioning
confidence: 99%
“…Although the pH of interstitial fluid along the slip zone was not measured, it was reported that pyrite was absent in the slip zone35. Because pyrite dissolution would lower the pH of the immediately surrounding sediment36, we used pH values of 3.0 and 6.0.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of new‐formed magnetic minerals is also an indicator of a certain degree of temperature elevation [ Chou et al ., ]. Pan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic studies conducted by Chou et al . [] indicated that pyrrhotite probably formed at high temperatures (>500°C) at the expense of pyrite in gouge within the principal slip zone of the Chi‐Chi earthquake. These studies indicate that rock magnetism can potentially detect frictional heating in earthquake slip zones.…”
Section: Introductionmentioning
confidence: 99%
“…[] and Chou et al . [] have already suggested that magnetite formed by frictional process. If it seems clear that the friction can cause new magnetic minerals, it is surprising that there is a concentration gradient between the PSZ and the rest of the gouge.…”
Section: Discussionmentioning
confidence: 99%
“…[] and Chou et al . [] (Figure a). The Verwey transition (120 K) is well identified in the deformed sediments and is not visible in the gouge.…”
Section: Rock Magnetismmentioning
confidence: 99%